Gambaran Burnout Pada Komunitas Pelari Rekreasional - Rifqi Rahmat Albari; Umi Anugrah Izzati (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
ABSTRACT This study aims to describe the phenomenon of burnout within a recreational running community in Surabaya. A descriptive qualitative approach was employed involving six participants—one community leader, two coaches, and three members—through in-depth interviews and participatory observations. The findings indicate three key manifestations of burnout that align with commonly recognized dimensions: emotional exhaustion, social withdrawal from community activities, and reduced personal accomplishment. These aspects are interrelated and influence runners’ motivation, training consistency, and social engagement within the community. The study highlights that burnout among recreational runners is a complex psychological phenomenon shaped by training demands, social pressures, and self-perceived performance. The findings offer practical implications for running communities to develop supportive structures and training load management strategies to prevent burnout among non-professional runners. In conclusion, this study successfully describes the burnout phenomenon as stated in the objectives, namely identifying the forms of burnout experiences experienced by recreational runners in their community activities Keywords: burnout, recreational runners, emotional exhaustion, sports community, motivation.